2021
DOI: 10.1596/1813-9450-9730
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration Economies in Developing Countries: A Meta-Analysis

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The agglomeration effect in the Netherlands doubled when the unit of analysis was changed from municipalities to NUTS-3 regions (Groot et al 2014). Through meta-analysis, Grover et al (2021) showed a higher gross agglomeration effect in developing countries. However, when the increasing congestion in developing countries is considered, the size of the agglomeration effect dramatically drops to the level seen in developed economies.…”
Section: Second-stage Regression Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The agglomeration effect in the Netherlands doubled when the unit of analysis was changed from municipalities to NUTS-3 regions (Groot et al 2014). Through meta-analysis, Grover et al (2021) showed a higher gross agglomeration effect in developing countries. However, when the increasing congestion in developing countries is considered, the size of the agglomeration effect dramatically drops to the level seen in developed economies.…”
Section: Second-stage Regression Resultsmentioning
confidence: 99%
“…The effect of local density on wages in Thailand was found to be greater than the effect of local density on wages in developed countries such as the Netherlands and France, where the impact of local density on wages was reported to be approximately 4-5% (Combes et al 2008;Groot et al 2014). Nevertheless, numerous factors could affect the degree of agglomeration, including the spatial scale and model specifications (Combes and Gobillon 2015;Grover et al 2021). The agglomeration effect in the Netherlands doubled when the unit of analysis was changed from municipalities to NUTS-3 regions (Groot et al 2014).…”
Section: Second-stage Regression Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, academia has not reached a consensus on the agglomeration effect, the importance of different agglomeration modes, or the transmission mechanism. Similarly, no clear conclusion exists concerning the relationship between agglomeration and innovation (Glaeser and Gottlieb, 2009;De Groot et al, 2015;Grover et al, 2021). The results of some empirical studies suggested that agglomeration could promote innovation (Paci and Usai, 1999;Chatterji et al, 2014;Jang et al, 2017), whereas others found that agglomeration had a negative infl uence or no infl uence on innovation (Boschma and Weterings, 2005;Rigby and Brown, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Later we will exploit the cross-sectional variation to attempt to control imperfectly for firm selection.Both quantity and quality effects described in the previous section can lead to inconsistent estimates. Though previous studies suggest that attempting to remedy this endogeneity does not drastically change the elasticity magnitudes (see meta-analysis byGrover, Lall and Timmis, 2021;Duranton 2016 for Colombia), we follow the literature by: (i) employing geological variables such as land fertility(Combes et al 2010), land suitability for the construction of tall buildings(Rosenthal and Strange 2008;Combes et al 2010) as instruments12 and (ii)…”
mentioning
confidence: 99%